THE RELATIONSHIPS BETWEEN KOREAN ADULT CHILDREN'S OUTCOMES AND THEIR PARENTS' PSYCHOLOGICAL WELLBEING. (11th November 2018) - Lim, M; Jun, H
Abstract: Guided by a life course perspective, the purpose of this study is to examine the linkages between adult children's outcomes for the transition to adulthood (employment, marital, and coresidence status) and their parents' psychological wellbeing, as well as whether these associations are similar for parental income. Regression models were estimated using data from 2, 596 parents whose youngest child was at least 40 years old in the 2012 (the 4th wave) KLOSA (Korean Longitudinal Study of Ageing). Sons' employment and marital status and daughters' marital status (excluding children's coresidence status) was significantly associated with their parents' levels of wellbeing. Moreover, parents' income moderated the associations between children's outcomes and the level of their parents' life satisfaction. Unemployed sons and single sons and daughters jeopardized the life satisfaction of their mothers with low income, but not other subgroups, and coresidence with sons decreased the life satisfaction of fathers with high income, but not those with low income. In line with how the results suggest that parental psychological outcomes regarding adult children's circumstances may be different depending on income, this study has implications for intergenerational relationships in the sociocultural context. These findings also imply that parents may have different views about norms regarding the transition to adulthood depending on their economic backgrounds. In sum, based on the life course perspective and a stress process model, this study provides a comprehensive understanding of how adult children and family structural factors may contribute to individuals' wellbeing in old age.